Monitoring of humoral immune responses against Marburg virus and evaluation of their role in protection against re-challenge in naturally immune Rousettus aegyptiacus fruit bats - Paweska, Janusz Tadeusz (University of Pretoria, 2019)
Thesis (PhD)--University of Pretoria, 2018.